2012
DOI: 10.1038/npp.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glutamate Levels in the Medial Prefrontal Cortex in Patients with Postpartum Depression

Abstract: The medial prefrontal cortex (MPFC) is a key brain area in depressive symptomatology; specifically, glutamate (Glu) has been reported to play a significant role in major depression (MD) in this area. MPFC Glu levels are sensitive to ovarian hormone fluctuations and pregnancy and the postpartum period are associated with the most substantial physiological alterations of female hormones. It is therefore logical to measure MPFC Glu levels in women with postpartum depression (PPD). Using in vivo magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 52 publications
3
56
1
3
Order By: Relevance
“…Another factor that could contribute to the adverse outcomes associated with gestational stress is glutamate [59][62]. A recent study has found that women with PPD have increased glutamate levels in the mPFC [19]. Repeated stress is also associated with increased glutamate neurotransmission in the mPFC [63] and excessive glutamate can lead to dendritic spine loss [64].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that could contribute to the adverse outcomes associated with gestational stress is glutamate [59][62]. A recent study has found that women with PPD have increased glutamate levels in the mPFC [19]. Repeated stress is also associated with increased glutamate neurotransmission in the mPFC [63] and excessive glutamate can lead to dendritic spine loss [64].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have shown abnormalities in ventral striatal response to reward (Moses-Kolko, EL et al, 2011), increased glutamate levels in the medial prefrontal cortex (McEwen, AM et al, 2012) and reduced postsynaptic serotonin-1A receptor binding, in particular in the ACC and mesiotemporal cortices (Moses-Kolko, EL et al, 2008). A single study (Epperson, CN et al, 2006) measured NAS.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Ketamine, a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, has been widely reported to have rapid antidepressant effects in both preclinical and clinical studies. 6,7 A single dose of ketamine exerted fast antidepressant effects within a few hours in patients with treatment-resistant major depression.…”
Section: Introductionmentioning
confidence: 99%